Records creating process in the Voivodeship Office in Tarnów: case of the Department of Religious Affairs (1975–1989) - Barbara Teresa Bielaszka-Podgórny (Archiwa - Kancelarie - Zbiory, 2020)
Records creating process is part of a broader concept of archives creating process, along with archiving process. Studying chanceries, i.e. reconstructing archives creating processes, plays an important role in reconstructing competencies, functions and action of records creators. The aim of the study is to present records creating processes that led to creating records of the Department of Religious Affairs (DoRA), a part of the Voivodeship Office in Tarnów. The article outlines the scope of formal competencies of the department and its activity in religious politics in the Tarnów voivodeship. Based on analysis of rich documentary evidence, the article describes office organization, circulation of not-classified records, process of creating records and forming records folders. The article ends with description of regulations regarding transmission of finalized cases records to institution’s archives. These questions were presented in context of analysis of office regulations and practice of department’s clerks. The article stresses lack of attentiveness in clerks practice and even infracting office regulation; this had a negative impact on records creation in DoRA. The source base for the article consisted of, primarily, archival materials created and collected by DoRA. Apart from that, all possible regulations were analysed, like regulations issued by the Voivode in Tarnów, office and archives regulations, adequate archival materials created by other departments of the Voivodeship Office in Tarnów.